Correlation between stem cell molecular phenotype and atherosclerotic plaque neointima formation and analysis of stem cell signal pathways - Shi, Chuanxin; Zhang, Kefan; Zhao, Zhenyu; Wang, Yifan; Xu, Haozhe; Wei, Wei (Frontiers in Cell and Developmental Biology, 2023)
Vascular stem cells exist in the three-layer structure of blood vessel walls and play an indispensable role in angiogenesis under physiological conditions and vascular remodeling under pathological conditions. Vascular stem cells are mostly quiescent, but can be activated in response to injury and participate in endothelial repair and neointima formation. Extensive studies have demonstrated the differentiation potential of stem/progenitor cells to repair endothelium and participate in neointima formation during vascular remodeling. The stem cell population has markers on the surface of the cells that can be used to identify this cell population. The main positive markers include Stem cell antigen-1 (Sca1), Sry-box transcription factor 10 (SOX10). Stromal cell antigen 1 (Stro-1) and Stem cell growth factor receptor kit (c-kit) are still controversial. Different parts of the vessel have different stem cell populations and multiple markers. In this review, we trace the role of vascular stem/progenitor cells in the progression of atherosclerosis and neointima formation, focusing on the expression of stem cell molecular markers that occur during neointima formation and vascular repair, as well as the molecular phenotypic changes that occur during differentiation of different stem cell types. To explore the correlation between stem cell molecular markers and atherosclerotic diseases and neointima formation, summarize the differential changes of molecular phenotype during the differentiation of stem cells into smooth muscle cells and endothelial cells, and further analyze the signaling pathways and molecular mechanisms of stem cells expressing different positive markers participating in intima formation and vascular repair. Summarizing the limitations of stem cells in the prevention and treatment of atherosclerotic diseases and the pressing issues that need to be addressed, we provide a feasible scheme for studying the signaling pathways of vascular stem cells involved in vascular diseases.